Pengaruh Terpaan Promosi Penjualan Shopee PayLater dan Persepsi Risiko Layanan Shopee PayLater terhadap Keputusan Pembelian Fashion menggunakan Shopee PayLater - Tiur Agata, Elisa; Pradekso, Tandiyo; Naryoso, Agus (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
This research addresses the rapidly growing trend of using pay later services in Indonesiain 2023, especially within the fashion sector. Shopee PayLater, one of the pay later services inIndonesia, has conducted sales promotions focused on enticing users with benefits such ascashback and other promotions, without providing education on the risks and obligations thatconsumers should understand before adopting the service. While this service offers benefits toconsumers in terms of meeting urgent needs, there are also notable risks, particularly concerningexcessive debt management, financial difficulties among the younger generation, and theescalating amount of unpaid debts within the pay later services in Indonesia.Using a positivist quantitative method, this research applies the Behavioral LearningTheory with the concept of Operant Conditioning to explain the influence of sales promotions,and the Risk Management Decision-Making Theory as a basis to understand the impact of riskperception on purchasing decisions. This study involved respondents aged 17-39 in theJabodetabek area who have been exposed to promotions and have either used or are currentlyusing Shopee PayLater. Regression analysis results indicate that sales promotions have a positiveinfluence of 14 percent on purchasing fashion products using Shopee PayLater, while riskperception has a negative influence of 28.2 percent. Consequently, Shopee PayLater needs tooptimize promotional messaging and enhance service security to manage consumer riskperception.